2009
DOI: 10.1063/1.3081632
|View full text |Cite
|
Sign up to set email alerts
|

Elastic buckling of AlN ribbons on elastomeric substrate

Abstract: For optoelectronic applications requiring unconventional substrates, use of flexible forms of semiconductors may be inevitable. We have fabricated a flexible form of single crystalline AlN ribbons with periodic and wavelike structures on an elastomeric substrate. Single crystalline AlN films were grown on Si (111) substrate using high vacuum unbalanced magnetron sputtering. Crystallinity of the AlN films was confirmed with x-ray diffraction and pole figure. The AlN ribbons were transferred to a prestrained (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Piezoelectric materials, such as lead zirconate titanate (PZT), [1][2][3][4] barium titanate (BaTiO 3 ), 5,6 aluminum nitride (AlN), 7 and zinc oxide (ZnO) [8][9][10][11] have been utilized to convert mechanical vibration energy into electrical energy for portable or self-powered electronics, among many other applications, such as solar cells. 12,13 Specifically, "piezoelectric nanogenerator," 8 first introduced in 2006, has boomed the applications of nano-scale piezoelectric materials for energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezoelectric materials, such as lead zirconate titanate (PZT), [1][2][3][4] barium titanate (BaTiO 3 ), 5,6 aluminum nitride (AlN), 7 and zinc oxide (ZnO) [8][9][10][11] have been utilized to convert mechanical vibration energy into electrical energy for portable or self-powered electronics, among many other applications, such as solar cells. 12,13 Specifically, "piezoelectric nanogenerator," 8 first introduced in 2006, has boomed the applications of nano-scale piezoelectric materials for energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…14 In order to accommodate the development of consumer electronics, piezoelectric nanogenerators are expected to be able to integrate with wearable or stretchable devices and different approaches with success to some extent, such as limited stretchability, have been attempted. 2,3,5,7,8 The deformability, i.e., bendability and stretchability, is realized by bonding buckled piezoelectric materials on top of soft materials. There are two limitations among existing work, namely, energy harvesting only at the high frequency domain and stretchability.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been found that superior power generation is realized by using bistable buckled beams. 9 Buckled piezoelectric beams (such as zirconate titanate, 10 aluminum nitride, 11 and zinc oxide 12 ) have also been used for stretchable energy harvesting.…”
mentioning
confidence: 99%